A Wireworm Conoderus rudis (Brown) (Insecta: Coleoptera: Elateridae) - Dakshina R. Seal (EDIS)
Wireworms are the larvae of click beetles. These larvae are smooth, slender, and round in cross-section. Wireworms are important pests of various crops and occur in all seasons at variable densities. Feeding damage is restricted to the seeds, seedlings, and underground parts of the plants. Unlike foliage feeders, they are very difficult to detect due to their soil-dwelling habitat. This 4-page fact sheet was written by Dakshina R. Seal and published by the UF Department of Entomology and Nematology, December 2011.